Using Inert Crystalline Materials as a Simulation for Energetic Materials - Mintoff, Alice (Cranfield University, 2023)
Researchers are aware that different crystal structures result in different materials properties. The understanding of a materials crystal structure is significant for materials development in multiple industries, from munitions to pharmaceuticals. The energetic material, HMX (octahydro-1,3,5,7-tetranitro-1,3,5,7-tetrazocine) is a commonly used energetic material and is found as a by-product in some manufacturing processes for RDX. HMX exists in multiple polymorphs and also exhibits a phenomenon known as crystal twinning. Experimentation of the co-crystallisation of paracetamol and seven other isomers and analogues yielded initial results that shows similar crystalline properties between paracetamol and HMX. Making paracetamol and ideal starting point for the development of the experimental techniques required to grown single crystal HMX. Eight isomers of paracetamol and 26 combinations within 3 different ratios have been identified as a starting point for looking into co-crystallisation, the process of two or more entities aggregating together in a crystal structure with no covalent bonding, with optical microscopy, Powder Xray Diffraction and Differential Scanning Calorimetry being employed as methods of analysis of the resulting crystals. Research into the co-crystallisation of paracetamol and the various isomers and polymorphs has yielded initial results that indicate that some co-crystallisation has occurred.
Keywords: Crystalline Materials; Energetics; HMX; DSDS22 Poster; DSDS22